Seizures in tramadol overdoses reported in the ToxIC registry: predisposing factors and the role of naloxone. (3rd August 2019) - Murray, Brian Patrick; Carpenter, Joseph E.; Dunkley, Camille A.; Moran, Tim P.; Alfaifi, Musa; Alsukaiti, Waleed S.; Kazzi, Ziad
Abstract: Importance : Tramadol prescriptions have increased as fewer schedule II and III drugs are prescribed. There has been a concomitant increase in overdoses and adverse events recorded in the National Poison Data System. Seizure activity after tramadol overdose or therapeutic use is a well-documented adverse event. The primary objective is to evaluate the characteristics associated with seizures following single agent tramadol ingestion. Secondarily we aim to compare the rate of seizures in individuals treated, and not treated, with naloxone. Methods : We searched the Toxicology Investigators Consortium data registry for all cases of single agent tramadol ingestions from 01/01/2014 through 12/31/2017. Descriptive statistics were used to evaluate characteristics associated with increased risk of seizures. Binary logistic regressions were used to evaluate the associations between seizures and age, race, acuity, intent, toxidromes, symptoms, and treatments. Results : There were 80 single ingestion tramadol cases entered into the registry. Seizures developed in 42 (52.5%) patients. Asian patients (OR = 7.2, 95% CI: 1.9–27.3, p = .004) and patients abusing or misusing tramadol (OR = 3.2, 95% CI: 1.2–8.3, p = .02) more likely to develop seizures. Patients exhibiting an opioid toxidrome were significantly less likely to develop seizures (OR = 0.12, 95% CI: 0.03–0.60). Ingestion of tramadol as a means of self-harm and age were not associated with an increased risk of seizures. There was no significant association between naloxone administration and seizures (OR = 0.30, 95% CI 0.07–1.25). Conclusions : Based on data from the ToxIC registry, tramadol induced seizures are more likely in Asian patients and those abusing or misusing the medication. There was no association found between the development of seizures and the use of naloxone.